PERBANDINGAN ABNORMAL RETURN DAN LIKUIDITAS SAHAM SEBELUM DAN SESUDAH STOCK SPLIT STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Harahap, Riris A.; Munthe, Kornel (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2023)
This study aims to determine the comparison of Abnormal Return and Stock Liquidity before and after a Stock Split in companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The population in this research is all companies listing the study on companies listed on the Indonesia Stock Exchange for the 2017-2020 period, totaling 713 companies. By using purposive sampling, 30 samples of companies that met the criteria and used the Event Study design approach were obtained. This study uses secondary data. The data analysis technique used was the Wilcoxon Signed Rank Test non-parametric statistical test. The results of this study indicate that there is no significant increase in the average abnormal return before and after the stock split. While the second hypothesis based on the results of the Wilcoxon signed rank test shows that there is a significant increase in the average stock liquidity before and after the stock split.